Neuronal traits of clonal cell lines derived by fusion of dorsal root ganglia neurons with neuroblastoma cells. - Platika, D (1985)
In an attempt to immortalize the gene products of single neurons, somatic cell hybrids were produced by fusion of embryonic rat dorsal root ganglion (DRG) neurons with mouse neuroblastoma cells. Embryonic day 13 rat DRGs were fused with mouse neuroblastoma cells deficient in hypoxanthine phosphoribosyltransferase (HPRT; IMP:pyrophosphate phosphoribosyltransferase, EC 2.4.2.8). The hybrid cells were selected in medium with 100 microM hypoxanthine/1 microM aminopterin/12 microM thymidine to eliminate the neuroblastoma cells and with cis-hydroxyproline to retard fibroblast growth. Of the 17 lines derived, 4 manifested neuronal properties and were cloned. These lines retain both rat and mouse chromosomes and synthesize characteristic rat and mouse isoenzymes. Neuronal gangliosides, action potentials, and extensive neurite-like processes are exhibited by these hybrid cells, properties characteristic of DRG neurons but not of the neuroblastoma parent. Each line manifests a unique combination of action-potential properties and cell-surface markers, suggesting the selective expression of subsets of DRG neuronal genes. All of these neuronal properties are expressed constitutively, without the need for chemical induction or mitotic inhibition, and stably, without diminution after at least 5 months in culture. These lines may prove useful in the identification and isolation of gene products that characterize individual or small subsets of DRG neurons.